A Novel Finding of Tribological and Mechanical Linking to Micro‐Convex Texture on Hydrophilic Composites Surface under Water‐Lubricating Conditions. Issue 5 (17th May 2022) - Liang, Xiang; Guo, Zhiwei; Li, Zhe; Qiu, Yikun; Wang, Zhikang; Yuan, Chengqing
Abstract : Inside Cover : In article number 2100844 by Zhiwei Guo and co‐workers, a hydrophilic composite consisting of thermoplastic polyurethane (TPU) and polyvinyl alcohol (PVA) fibers is designed, which can spontaneously produce many micron‐level micro‐convex textures on the surface when immersed in water for a period of time. The hydrodynamic lubrication effect and cavitation effect caused by these micro‐convex textures endow the composite with excellent tribological properties, and the micro‐convex textures will not disappear completely with the friction process.